2019
DOI: 10.21608/bvmj.2019.119829
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pathological Studies on Kidneys affections in slaughtered farm animals

Abstract: The aim of this study was to detect the comparative pathological affections in kidneys of cattle and sheep. A total number of 192 kidney samples showing different pathological lesions were collected from El-basatin abattoir in Cairo-Egypt; 69 samples were collected from cattle and 123 samples were collected from sheep, respectively. Microscopically, the highest incidence of occurrence of renal interstitial nephritis was found to be 17.39% in cattle and 28.45% in sheep, followed by glomerulonephritis 21.73% in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The overall prevalence of hydatid cysts among the examined animals was 0.96%, with cattle exhibiting a significantly higher infection rate of 1.05% compared to buffaloes at 0.55%. This disparity highlights the increased vulnerability of cattle to hydatid infections in the study's context, and our results align with previous studies comparing the prevalence of hydatid cysts in Egyptian cattle and buffaloes have reported rates of 1.83% and 2.34% by Hassanin et al (2013), 0.61% and 0.2% by Borai et al (2013), and 0.4% for both species by Barghash et al (2017). The observed prevalence aligns closely with these previous Egyptian reports.…”
Section: Discussionsupporting
confidence: 92%
“…The overall prevalence of hydatid cysts among the examined animals was 0.96%, with cattle exhibiting a significantly higher infection rate of 1.05% compared to buffaloes at 0.55%. This disparity highlights the increased vulnerability of cattle to hydatid infections in the study's context, and our results align with previous studies comparing the prevalence of hydatid cysts in Egyptian cattle and buffaloes have reported rates of 1.83% and 2.34% by Hassanin et al (2013), 0.61% and 0.2% by Borai et al (2013), and 0.4% for both species by Barghash et al (2017). The observed prevalence aligns closely with these previous Egyptian reports.…”
Section: Discussionsupporting
confidence: 92%
“…El-Mashad et al . [ 10 ] found that 17.4% of cattle kidney samples collected from a Cairo slaughterhouse had IN, compared to 28.5% in sheep. For glomerulonephritis, the prevalence is higher in our study than that in the El-Mashad et al .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates in the literature vary widely. El-Mashad et al [10] found that 17.4% of cattle kidney samples collected from a Cairo slaughterhouse had IN, compared to 28.5% in sheep. For glomerulonephritis, the prevalence is higher in our study than that in the El-Mashad et al [10] study, at 22% and 26% of the cattle and sheep samples, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 Several reports in the literature refer to the common occurrence of renal infarcts in sheep, particularly identified at slaughter, however these studies did not perform further analysis or speculation regarding causes of the renal infarcts beyond the potential of septic emboli from previous bacterial infections. 2 , 7 The lack of a definitive cause of infarcts in sheep is likely a combination of the abundance of underlying causes and difficulty in determining when the infarction occurred. Causes of thrombosis in all species include any factor altering the components of Virchow’s triad (vascular injury, hypercoagulability, and abnormal blood flow), with endothelial damage being cited as the most important factor.…”
Section: Discussionmentioning
confidence: 99%